A study of micro to nano structure fine solid line printing for graphene ink by micro-flexographic printing method - Hassan, Suhaimi; Yusof, Mohd Sallehuddin; Maksud, Mohd Idris; Nodin, Muhamad Nor (IARAS Pub, 2016)
Flexography is one of the famous printing techniques that are possible to create graphic and electronic device on variable substrates by using conductive ink. Graphene is an example of material that can be used as printing ink which usually use in producing micro to nano scale electronic devices in a low cost production. Flexography is a high speed roll to roll printing technique commonly used in paper printing industry. And this study elaborates the analysis of graphene as a printing ink use in combination of flexography and micro-contact which known as micro-flexographic printing for micro to nano scale fine solid line image. Here, it is proposed that extending micro-flexographic printing technique into the multiple micro to nano scale printing fine solid line onto biaxially oriented polypropylene (BOPP) substrate by using graphene as a printing ink. This paper will illustrates the use of graphene in producing multiple fine lines printing capability for the application of printing electronic, graphic and bio-medical.